2014
DOI: 10.7314/apjcp.2014.15.20.8987
|View full text |Cite
|
Sign up to set email alerts
|

Definitive Concurrent Chemoradiotherapy in Cervical Cancer - a University of Malaya Medical Centre Experience

Abstract: 2 ) concurrent with daily EBRT to pelvis of 45-50Gy followed by low dose rate brachytherapy or EBRT boost to tumour. Local control rate, progression free survival, overall survival and treatment related toxicities graded by the RTOG criteria were evaluated. Results: The mean age was 56. At the median follow-up of 72 months, the estimated 5-year progression-free survival (PFS) (median PFS 39 months) and the 5-year overall survival (OS) (median OS 51 months) were 48% and 50% respectively. The 5-year local contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Multiple factors including bacteria, viruses, microbes, precocious sexuality, promiscuity, multiple birth, and genetic susceptibility can cause cervical lesions and even cervical cancer (Zamaniah et al, 2014;Zeng et al, 2014). Numerous epidemiologic and molecular biology studies have confirmed that the HPV is closely related to the occurrence and development of genital tract epithelial malignant tumors and precancerous lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple factors including bacteria, viruses, microbes, precocious sexuality, promiscuity, multiple birth, and genetic susceptibility can cause cervical lesions and even cervical cancer (Zamaniah et al, 2014;Zeng et al, 2014). Numerous epidemiologic and molecular biology studies have confirmed that the HPV is closely related to the occurrence and development of genital tract epithelial malignant tumors and precancerous lesions.…”
Section: Discussionmentioning
confidence: 99%
“…A significant proportion of our patients attend our centre from distant places and a gap between EBRT (external beam radiotherapy) and ICBT is frequently observed making treatment prolonged and protracted upto 10 weeks and beyond due to social reasons. Zamaniah et al (2014) observed that nearly 30% exceeded the recommended 7 weeks for treatment completion due to various reasons. It was hypothesised that a shorter treatment time within the tolerance limit will accomplish the RTOG/GOG (Gynaecologic Oncologgy Group) recommendations of overall treatment time and might improve treatment compliance.…”
Section: Impact Of Treatment Time On Chemoradiotherapy In Locallymentioning
confidence: 99%